Hydrophobic sealing film material as well as preparation method and application thereof
By using polyethylene resin and polyisobutylene resin in the sealing film material to form a bicontinuous phase structure, and combining solid paraffin, nano-opening modifiers, micro-crosslinking modifiers and hydrophobic modifiers, a super-hydrophobic modifier was prepared. The hydrophobic sealing film material has high performance and high durability, which solves the problem in the existing technology that the sealing film material is difficult to have both super hydrophobicity and durability.
Patent Information
- Application Number
- CN202411608977.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
AI Technical Summary
The existing sealing film materials are difficult to have both superhydrophobicity and durability, and are easy to slip off during sealing and use, so they cannot effectively protect anhydrous substances.
A hydrophobic sealing film material is prepared by melt blending, using polyethylene resin and polyisobutylene resin to form a bicontinuous phase structure, and dispersing solid paraffin and nano-opening modifiers in the resin, combining micro-crosslinking modifiers and hydrophobic Modifiers to construct microfluidic channels to improve compatibility and dispersion concentration.
The sealing film material achieves super hydrophobicity and high durability, and can be knotted without slipping when used for sealing. It can be used on irregular and wrinkled surfaces to prevent sample evaporation and contamination, and has higher biological safety.
Smart Images

Figure CN119331330A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a hydrophobic sealing film material and a preparation method and application thereof. Background Art
[0002] Parafilm is a kind of special polymer film that can be automatically sealed, molded, and has good toughness. Parafilm can be used to quickly and effectively seal laboratory vessels. It has waterproof and moisture-proof properties, can effectively prevent the volatilization and contamination of samples in laboratory vessels, and protect anhydrous substances. How to prepare super-hydrophobic and durable parafilm materials is a hot topic in this field. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a hydrophobic sealing film material and a preparation method and application thereof. The sealing film made of the resin material provided by the present invention has very excellent hydrophobicity and durability.
[0004] The present invention provides a hydrophobic sealing film material, which is prepared by melt blending raw materials, and the raw materials include, by weight:
[0005]
[0006] The polyethylene resin and the polyisobutylene resin in the hydrophobic sealing film material are a dual-continuous phase structure in terms of microscopic thermodynamic phase structure, and the solid paraffin is dispersed in the resin continuous phase structure in an island-like structure.
[0007] Preferably, the polyethylene resin is a low-density polyethylene resin; the melt flow rate of the polyethylene resin at 210° C. is 4 to 20 g / 10 min; and the elongation at break of the polyethylene resin is not less than 200%.
[0008] Preferably, the number average molecular weight of the polyisobutylene resin is 400-5000.
[0009] Preferably, the melting point of the solid paraffin is 50-70°C.
[0010] Preferably, the compatibilizer is at least one of SIS petroleum resin, EPDM rubber, EPDM rubber, polyolefin elastomer, styrene-butadiene block copolymer and hydrogenated styrene-butadiene block copolymer.
[0011] Preferably, the nano-opening modifier is at least one of nano-silicon dioxide, nano-montmorillonite, nano-wollastonite, nano-titanium dioxide, nano-zinc oxide and nano-calcium carbonate; and the particle size of the nano-opening modifier is 400-1000 meshes.
[0012] Preferably, the micro-crosslinking modifier is at least one of dibenzoyl peroxide, diisopropylbenzene peroxide and azobisisobutyronitrile.
[0013] Preferably, the hydrophobic modifier is at least one of a fatty acid compound, a silane compound and a thiol compound.
[0014] The present invention provides a method for preparing the hydrophobic sealing membrane material described in the above technical solution, comprising the following steps:
[0015] Polyethylene resin, polyisobutylene resin, solid paraffin, a compatibilizer, a nano-opening modifier, a micro-crosslinking modifier and a hydrophobic modifier are melt-blended to obtain a hydrophobic sealing film material.
[0016] The present invention provides a hydrophobic sealing membrane, the material of the hydrophobic sealing membrane is the hydrophobic sealing membrane material described in the above technical solution.
[0017] Compared with the prior art, the present invention provides a hydrophobic sealing film material and its preparation method and application. The hydrophobic sealing film material provided by the present invention is made of raw materials by melt blending, and the raw materials include, by mass, 100 parts of polyethylene resin, 20 to 50 parts of polyisobutylene resin, 0.1 to 10 parts of solid paraffin, 0.03 to 2.5 parts of compatibilizer, 0.1 to 5 parts of nano-opening modifier, 0.05 to 1 part of micro-crosslinking modifier, and 0.5 to 5 parts of hydrophobic modifier; the polyethylene resin and polyisobutylene resin in the hydrophobic sealing film material are a dual-continuous phase structure in the microscopic thermodynamic phase structure, and the solid paraffin is dispersed in the resin continuous phase structure in an island-like structure. In the present invention, the polyisobutylene (PIB) resin and the solid paraffin are a dual-continuous phase structure with the polyethylene (PE) resin phase under the action of the compatibilizer and the micro-crosslinking modifier in the microscopic thermodynamic phase structure. The present invention constructs a dual-continuous phase structure, which can not only improve the dispersion concentration of low surface energy substances in the blend system at the microscopic interface layer, but also ensure that the hydrophobic sealing film prepared by the technology of the present invention has both low tensile strength and high elongation at break, can quickly and effectively seal experimental vessels, has waterproof and moisture-proof properties to effectively prevent sample volatilization and contamination, effectively protects anhydrous substances, can be folded and used repeatedly, and will not be torn when wrapped around sharp objects, and has the application of stretching and wrapping sealing of sealing films; further, by utilizing the microfluidic channels in the dual-continuous phase structure, using micro-crosslinking The modifier is melt blended and grafted with polyethylene (PE) resin, polyisobutylene (PIB) resin and solid paraffin, which can not only improve the thermodynamic compatibility of the two phases in the blending system, but also further improve the dispersion concentration of low surface energy substances in the microscopic interface layer in the blending system, so that the sealing film material can achieve hydrophobic and super hydrophobic applications, and has high durability and excellent flexibility. It can be tied in a knot when used for sealing, and the knot will not slip off, and can even be used on irregular and wrinkled surfaces. Even when the sealed container is accidentally dropped, it will not cause leakage, which is convenient for cleaning. The experimental results show that the hydrophobic sealing film prepared by the technology of the present invention does not contain any fluoride or halide, has higher biological safety, has a contact angle of ≥120° to pure water, and has a tensile strength and elongation at break of ≥200%. It can be tied in a knot when used for sealing, and the knot will not slip off. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0019] Figure 1is a surface SEM image of the hydrophobic sealing membrane provided in Example 1 of the present invention at room temperature;
[0020] Figure 2 This is a diagram showing the effect of a centrifuge tube sealed with a hydrophobic sealing membrane provided in Example 1 of the present invention after being placed at room temperature for 7 days;
[0021] Figure 3 This is a diagram showing the effect of the hydrophobic sealing membrane provided in Example 1 of the present invention after being tied into a knot and placed at room temperature for 7 days. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The present invention provides a hydrophobic sealing film material, which is prepared by melt blending raw materials, and the raw materials include, by weight:
[0024]
[0025] The polyethylene resin and the polyisobutylene resin in the hydrophobic sealing film material are a dual-continuous phase structure in terms of microscopic thermodynamic phase structure, and the solid paraffin is dispersed in the resin continuous phase structure in an island-like structure.
[0026] In the hydrophobic sealing film material provided by the present invention, the polyethylene (PE) resin is preferably a low-density polyethylene (LDPE) resin; the melt flow rate of the polyethylene (PE) resin at 210°C is preferably 4 to 20 g / 10min, specifically 4 g / 10min, 5 g / 10min, 6 g / 10min, 7 g / 10min, 8 g / 10min, 9 g / 10min, 10 g / 10min, 11 g / 10min, 12 g / 10min, 13 g / 10min, 14 g / 10min, 15 g / 10min, 16 g / 10min, 17 g / 10min, 18 g / 10min, 19 g / 10min or 20 g / 10min; the elongation at break of the polyethylene (PE) resin is preferably not less than 200%, more preferably not less than 250%.
[0027] In the hydrophobic sealing film material provided by the present invention, the number average molecular weight of the polyisobutylene (PIB) resin is preferably 400-5000, specifically 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 2000, 2500, 3000, 3500, 4000, 4500 or 5000. In the present invention, the polyisobutylene (PIB) resin is more preferably a mixture of a polyisobutylene (PIB) resin having a number average molecular weight of 400-1500 and a polyisobutylene (PIB) resin having a number average molecular weight of 3000-5000, and the mass ratio of the polyisobutylene (PIB) resin having a number average molecular weight of 400-1500 and a polyisobutylene (PIB) resin having a number average molecular weight of 3000-5000 is preferably (1-10):1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0028] In the hydrophobic sealing film material provided by the present invention, the beneficial effects of using polyisobutylene are mainly: as a typical saturated linear polymer, polyisobutylene is similar to polyethylene in molecular structure and has good compatibility with polyethylene molecules in thermodynamics. At the same time, the tensile elongation at break of the blend can be further increased, and the tensile performance of the prepared hydrophobic sealing film material can be improved; more importantly, the polyisobutylene with a number average molecular weight of 400 to 5000 preferably used in the present invention has a moderate melt viscosity in the processing temperature range of 160 to 230°C, and in the present invention, it is compatible with polyethylene. When the polyisobutylene matrix material is blended and processed, the shear field can be controlled by selecting the screw type of twin-screw extrusion, controlling the screw speed, controlling the extrusion pressure during extrusion molding, etc., so that the polyisobutylene phase can exist in the polyethylene phase as a continuous phase in the microscopic phase structure, thereby increasing the performance of the prepared hydrophobic sealing film material; at the same time, under the action of cross-linking modifiers such as dibenzoyl oxide, diisopropylbenzene peroxide, and azobisisobutyronitrile used in the present invention, the polyisobutylene can further undergo cross-linking reaction with polyethylene and paraffin to improve the thermodynamic compatibility with polyethylene and paraffin.
[0029] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the polyisobutylene (PIB) resin in the raw material may specifically be 20 parts by mass, 21 parts by mass, 22 parts by mass, 23 parts by mass, 24 parts by mass, 25 parts by mass, 26 parts by mass, 27 parts by mass, 28 parts by mass, 29 parts by mass, 30 parts by mass, 31 parts by mass, 32 parts by mass, 33 parts by mass, 34 parts by mass, 35 parts by mass, 36 parts by mass, 37 parts by mass, 38 parts by mass, 39 parts by mass, 40 parts by mass, 41 parts by mass, 42 parts by mass, 43 parts by mass, 44 parts by mass, 45 parts by mass, 46 parts by mass, 47 parts by mass, 48 parts by mass, 49 parts by mass, 49.5 parts by mass or 50 parts by mass.
[0030] In the hydrophobic sealing film material provided by the present invention, the melting point of the solid paraffin is preferably 50-70°C, specifically 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C.
[0031] The beneficial effects of the solid paraffin used in the hydrophobic sealing film material provided by the present invention are mainly: the solid paraffin is mainly composed of n-docosahexadecane and n-octacosane, which, as a typical long-chain aliphatic hydrocarbon compound, has a high melting point and a low solubility, and not only has good hydrophobic properties, but also has better biological safety compared with fluorine-containing compounds; more importantly, within the processing temperature range of 160 to 230° C., its melt viscosity is moderate, and when blended with polyethylene and polyisobutylene matrix materials in the present invention, the screw type of twin-screw extrusion, the control of screw speed, and extrusion molding can be selected. By controlling the extrusion pressure and other shear fields, the polyethylene resin and the polyisobutylene resin in the hydrophobic sealing film material can be realized as a dual-continuous phase structure in the microscopic phase structure, and the solid paraffin is dispersed in the resin continuous phase structure in an island-like structure to increase the content concentration of the paraffin phase with low surface energy in the interface layer, and further improve the hydrophobic performance of the blend; at the same time, under the action of cross-linking modifiers such as dibenzoyl oxide, diisopropylbenzene peroxide, and azobisisobutyronitrile used in the present invention, the solid paraffin can further undergo cross-linking reaction with polyethylene and polyisobutylene to improve the thermodynamic compatibility of paraffin with polyethylene and polyisobutylene.
[0032] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the solid paraffin in the raw material may specifically be 0.1 parts by mass, 0.5 parts by mass, 1 parts by mass, 1.5 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass, 5 parts by mass, 5.5 parts by mass, 6 parts by mass, 6.5 parts by mass, 7 parts by mass, 7.5 parts by mass, 8 parts by mass, 8.25 parts by mass, 8.5 parts by mass, 9 parts by mass, 9.5 parts by mass or 10 parts by mass.
[0033] In the hydrophobic sealing membrane material provided by the present invention, the compatibilizer is preferably at least one of SIS petroleum resin, ethylene propylene diene monomer rubber (EPR), ethylene propylene diene monomer rubber (EPDM), polyolefin elastomer (POE), styrene-butadiene block copolymer (SBS) and hydrogenated styrene-butadiene block copolymer (SEBS), more preferably at least one of SIS petroleum resin, ethylene propylene diene monomer rubber (EPDM), polyolefin elastomer (POE) and hydrogenated styrene-butadiene block copolymer (SEBS), most preferably multiple of polyolefin elastomer (POE), hydrogenated styrene-butadiene block copolymer (SEBS) and SIS petroleum resin, and the mass ratio of the polyolefin elastomer (POE), hydrogenated styrene-butadiene block copolymer (SEBS) and SIS petroleum resin is preferably (0-3):(0-3):0.25, more preferably (0-2):(0-2):0.25.
[0034] In the hydrophobic sealing film material provided by the present invention, the beneficial effect of the compatibilizer used is mainly: its molecular structure is similar to the polyethylene and polyisobutylene in the main raw materials of the hydrophobic sealing film material provided by the present technology, while increasing the thermodynamic compatibility of polyethylene and polyisobutylene, so as to further ensure that the polyisobutylene phase exists in the polyethylene phase as a continuous phase during the twin-screw extrusion molding of the hydrophobic sealing film material.
[0035] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the compatibilizer in the raw material may specifically be 0.03 parts by mass, 0.05 parts by mass, 0.075 parts by mass, 0.1 parts by mass, 0.25 parts by mass, 0.5 parts by mass, 0.75 parts by mass, 1 parts by mass, 1.25 parts by mass, 1.5 parts by mass, 1.75 parts by mass, 2 parts by mass, 2.25 parts by mass or 2.5 parts by mass.
[0036] In the hydrophobic sealing film material provided by the present invention, the nano-opening modifier is preferably at least one of nano-silicon dioxide, nano-montmorillonite, nano-wollastonite, nano-titanium dioxide, nano-zinc oxide and nano-calcium carbonate; the particle size of the nano-opening modifier is preferably 400-1000 mesh, specifically 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, 650 mesh, 700 mesh, 750 mesh, 800 mesh, 850 mesh, 900 mesh, 950 mesh or 1000 mesh.
[0037] In the hydrophobic sealing film material provided by the present invention, the effective purpose of the nano-opening modifier used is mainly: it can make the surface of the prepared hydrophobic sealing film material produce bulges, infiltrate air to reduce the negative pressure between the films, thereby separating the films and increasing the opening of the prepared hydrophobic sealing film material; at the same time, the nano-opening modifier used itself has a certain hydrophobicity, and during the blending process, it can synergize with the paraffin and hydrophobic modifier used in the present technology to further improve the hydrophobic properties of the hydrophobic sealing film material provided by the present technology; further, the nano-opening modifier used can also play the role of a polyethylene nucleating agent, by further refining the grain size of the polyethylene during the crystallization process, so as to further improve the light transmittance of the final product.
[0038] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the nano-opening modifier in the raw material may specifically be 0.1 parts by mass, 0.2 parts by mass, 0.3 parts by mass, 0.4 parts by mass, 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, 0.9 parts by mass, 1 parts by mass, 1.2 parts by mass, 1.5 parts by mass, 1.7 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 3.5 parts by mass, 4 parts by mass, 4.5 parts by mass or 5 parts by mass.
[0039] In the hydrophobic sealing film material provided by the present invention, the micro-crosslinking modifier is preferably at least one of dibenzoyl peroxide (BPO), dicumyl peroxide (DCP) and azobisisobutyronitrile (AIBN).
[0040] The beneficial effect of the micro-crosslinking modifier used in the hydrophobic sealing film material provided by the present invention is mainly that the micro-crosslinking modifier can form reaction activation points in the molecular chains of polyethylene, polyisobutylene and paraffin, and through the crosslinking reaction between the activation points, the thermodynamic compatibility of polyisobutylene and paraffin with polyethylene is improved, while further ensuring that the polyisobutylene phase exists in the polyethylene phase as a continuous phase during the twin-screw extrusion molding of the hydrophobic sealing film material.
[0041] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the micro-crosslinking modifier in the raw material may specifically be 0.05 parts by mass, 0.07 parts by mass, 0.1 parts by mass, 0.15 parts by mass, 0.2 parts by mass, 0.25 parts by mass, 0.3 parts by mass, 0.4 parts by mass, 0.5 parts by mass, 0.6 parts by mass, 0.7 parts by mass, 0.8 parts by mass, 0.9 parts by mass or 1 part by mass.
[0042] In the hydrophobic sealing film material provided by the present invention, the hydrophobic modifier is preferably at least one of a fatty acid compound, a long-chain silane compound and a long-chain thiol compound, more preferably stearic acid, calcium stearate, barium stearate, zinc stearate, trimethoxysilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, n-hexylthiol, n-dodecylthiol, n-tetradecylthiol, n-hexadecylthiol, n-octadecylthiol, n-eicosylthiol and n-docosylthiol, more preferably stearic acid, trimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, n-hexadecylthiol, n-octadecylthiol, n-eicosylthiol and n-docosylthiol, most preferably at least one of stearic acid, trimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, n-hexadecylthiol, n-octadecylthiol and n-eicosylthiol. In one embodiment provided by the present invention, the hydrophobic modifier is a mixture of n-hexadecylmercaptan and octadecyltrimethoxysilane, and the mass ratio of n-hexadecylmercaptan to octadecyltrimethoxysilane is preferably 1:
[0043] (0.5~2), more preferably 1:1.
[0044] In the hydrophobic sealing film material provided by the present invention, the effective purpose of the hydrophobic modifier used is mainly: the hydrophobic modifier used is similar to polyethylene, polyisobutylene and paraffin molecules in the main structure of the molecular chain, and its main function is to synergize with paraffin to further improve the hydrophobic properties of the hydrophobic sealing film material provided by the present technology, and at the same time, the refractive index is low, which can ensure the light transmittance of the final product; at the same time, the hydrophobic modifier used does not contain any fluoride or halide, and has higher biological safety.
[0045] In the hydrophobic sealing film material provided by the present invention, based on the content of the polyethylene (PE) resin in the raw material as 100 parts by mass, the content of the hydrophobic modifier in the raw material may specifically be 0.5 parts by mass, 0.7 parts by mass, 1 parts by mass, 1.2 parts by mass, 1.5 parts by mass, 1.7 parts by mass, 2 parts by mass, 2.3 parts by mass, 2.5 parts by mass, 2.7 parts by mass, 3 parts by mass, 3.2 parts by mass, 3.5 parts by mass, 3.7 parts by mass, 4 parts by mass, 4.2 parts by mass, 4.5 parts by mass, 4.7 parts by mass or 5 parts by mass.
[0046] The present invention also provides a method for preparing the hydrophobic sealing membrane material described in the above technical solution, comprising the following steps:
[0047] Polyethylene resin, polyisobutylene resin, solid paraffin, a compatibilizer, a nano-opening modifier, a micro-crosslinking modifier and a hydrophobic modifier are melt-blended to obtain a hydrophobic sealing film material.
[0048] In the preparation method provided by the present invention, the raw material information and dosage ratio of the polyethylene resin, polyisobutylene resin, solid paraffin, compatibilizer, nano-opening modifier, micro-crosslinking modifier and hydrophobic modifier have been introduced in the previous text and will not be repeated here.
[0049] In the preparation method provided by the present invention, the polyethylene resin, polyisobutylene resin, solid paraffin, compatibilizer, nano-opening modifier, micro-crosslinking modifier and hydrophobic modifier are preferably premixed before melt blending, and the premixing time is preferably 5 to 30 minutes, specifically 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.
[0050] In the preparation method provided by the present invention, the temperature of the melt blending is preferably 160-250°C, specifically 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C or 250°C.
[0051] In the preparation method provided by the present invention, the melt blending is preferably carried out in a twin-screw extruder; the screw speed of the twin-screw extruder is preferably 80-200rpm, specifically 80rpm, 90rpm, 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm.
[0052] In the preparation method provided by the present invention, after melt blending, the mixture is extruded, cooled, granulated and dried to obtain a hydrophobic sealing film material.
[0053] The present invention also provides a hydrophobic sealing film, the material of which is the hydrophobic sealing film material described in the above technical solution. In the present invention, the preparation method of the sealing film includes but is not limited to one or more of extrusion molding, blow molding, calendering molding and cast molding.
[0054] The technical solution provided by the present invention can not only improve the dispersion concentration of low surface energy substances in the microscopic interface layer in the blend system by constructing a dual-continuous phase structure; it can also ensure that the hydrophobic sealing film prepared by the technology of the present invention has both low tensile strength and high elongation at break, can quickly and effectively seal experimental vessels, has waterproof and moisture-proof properties to effectively prevent sample volatilization and contamination, effectively protects anhydrous substances, can be folded and used repeatedly, and will not be torn when wrapped around sharp-shaped objects, and has the application of stretching and wrapping sealing of the sealing film; further, by utilizing the dual-continuous phase structure In the microfluidic channel, a micro-cross-linking modifier is used to carry out melt blending grafting reaction with polyethylene resin, polyisobutylene resin and solid paraffin, which can not only improve the thermodynamic compatibility of the two phases in the blending system, but also further improve the dispersion concentration of low surface energy substances in the microscopic interface layer in the blending system, so that the sealing film material can achieve hydrophobic and super-hydrophobic applications while having excellent flexibility. It can be tied into a knot when used for sealing, and the knot will not slip off, and can even be used on irregular and wrinkled surfaces. Even if the sealed container is accidentally dropped, it will not cause leakage, which facilitates cleaning.
[0055] Experimental results show that the hydrophobic sealing film prepared by the technology of the present invention does not contain any fluoride or halide, has higher biological safety, has a contact angle of ≥120° to pure water, and has a tensile strength and elongation at break of ≥200%. It can be tied into a knot when used for sealing without slipping off.
[0056] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0057] Example 1
[0058] 1) Weigh 100 parts by weight of low-density polyethylene (LDPE) resin (melt flow rate at 210°C: 4 g / 10 min, elongation at break: 250%, brand: LD160AS, origin: Beijing Yanshan Petrochemical Co., Ltd., China Petrochemical Group, the same below), 8.25 parts by weight of polyisobutylene (PIB) resin (number average molecular weight: 4500, origin: BASF China Ltd., Germany, the same below), 41.25 parts by weight of polyisobutylene (PIB) resin (number average molecular weight: 1300, origin: BASF China Ltd., Germany, the same below), 8.25 parts by weight of solid paraffin (melting point: 65°C-70°C, origin: Sinopharm Chemical Reagent Co., Ltd., the same below), 0.25 parts by weight of SIS petroleum resin (brand: 5400, origin: ExxonMobil Petrochemical Oil Company, the same below), 0.6 parts by mass of silicon dioxide (particle size: 800-1000 mesh, origin: Sinopharm Chemical Reagent Co., Ltd., the same below), 0.05 parts by mass of diisopropylbenzene peroxide (DCP) (brand: AR, origin: Sinopharm Chemical Reagent Co., Ltd., the same below), 1.0 parts by mass of n-hexadecylmercaptan (brand: AR, origin: Sinopharm Chemical Reagent Co., Ltd., the same below), 1.0 parts by mass of octadecyltrimethoxysilane (brand: AR, origin: Sinopharm Chemical Reagent Co., Ltd., the same below), placed in a high-speed mixer (model: SHR-5, manufacturer: Zhangjiagang Huanfeng Machinery Factory, the same below), taken out after mixing for 5 minutes, and placed in the hopper of a twin-screw extruder (model: CTE-20, manufacturer: Nanjing Coperion Co., Ltd., the same below);
[0059] 2) Setting the feeding rate of the feeder of the twin-screw extruder to 200 rpm, setting the screw temperature of the twin-screw extruder from the feed hopper to the die to 160-230° C.; setting the screw speed of the screw extruder to 140 rpm;
[0060] 3) cooling and granulating the melt mixture of polyethylene (PE) resin / polyisobutylene (PIB) resin / solid paraffin / compatibilizer / nano-opening modifier / micro-crosslinking modifier / hydrophobic modifier extruded by a screw extruder, and drying to obtain a hydrophobic sealing film material;
[0061] 4) The hydrophobic sealing film material was placed in a film casting machine (model: XH-432, origin: Dongguan Xihua Testing Instrument Co., Ltd., the same below), the casting extrusion temperature was set to 220°C, and a film sample with a thickness of 0.1 mm was extruded. The test results of the film sample are as follows: Figures 1 to 3 And as shown in Table 1.
[0062] Example 2
[0063] 1) Weigh 100 parts by mass of low-density polyethylene (LDPE) resin, 16.5 parts by mass of polyisobutylene (PIB) resin (number average molecular weight: 4500), 33.0 parts by mass of polyisobutylene (PIB) resin (number average molecular weight: 1300), 8.25 parts by mass of solid paraffin, 0.25 parts by mass of SIS petroleum resin, 2.0 parts by mass of polyolefin elastomer (POE) (brand: 6102FL, origin: ExxonMobil (Huizhou) Chemical Co., Ltd., the same below), 0.6 parts by mass of silicon dioxide, 0.05 parts by mass of diisopropylbenzene peroxide (DCP), 1.0 parts by mass of n-hexadecyl mercaptan, and 1.0 parts by mass of octadecyltrimethoxysilane, place them in a high-speed mixer, mix for 5 minutes, take them out, and place them in the feeding hopper of a twin-screw extruder;
[0064] 2) Setting the feeding rate of the feeder of the twin-screw extruder to 200 rpm, setting the screw temperature of the twin-screw extruder from the feed hopper to the die to 160-230° C.; setting the screw speed of the screw extruder to 140 rpm;
[0065] 3) cooling and granulating the melt mixture of polypropylene resin / solid paraffin / compatibilizer / micro-crosslinking modifier / hydrophobic modifier / inorganic nano powder extruded by a screw extruder, and drying to obtain a hydrophobic sealing film material;
[0066] 4) The hydrophobic sealing film material was placed in a film casting machine, the casting extrusion temperature was set to 220° C., and a film sample with a thickness of 0.1 mm was extruded. The test results of the film sample are shown in Table 1.
[0067] Example 3
[0068] 1) Weigh 100 parts by mass of low-density polyethylene (LDPE) resin, 16.5 parts by mass of polyisobutylene (PIB) resin (number average molecular weight: 4500), 33.0 parts by mass of polyisobutylene (PIB) resin (number average molecular weight: 1300), 8.25 parts by mass of solid paraffin, 0.25 parts by mass of SIS petroleum resin, 2.0 parts by mass of hydrogenated styrene-butadiene block copolymer (SEBS) (brand: G6152E, origin: Kraton Polymer Trading (Shanghai) Co., Ltd.), 0.6 parts by mass of silicon dioxide, 0.05 parts by mass of diisopropylbenzene peroxide (DCP), 1.0 parts by mass of n-hexadecylmercaptan, and 1.0 parts by mass of octadecyltrimethoxysilane, place them in a high-speed mixer, mix for 5 minutes, take them out, and place them in the feeding hopper of a twin-screw extruder;
[0069] 2) Setting the feeding rate of the feeder of the twin-screw extruder to 200 rpm, setting the screw temperature of the twin-screw extruder from the feed hopper to the die to 160-230° C.; setting the screw speed of the screw extruder to 140 rpm;
[0070] 3) cooling and granulating the melt mixture of polypropylene resin / solid paraffin / compatibilizer / micro-crosslinking modifier / hydrophobic modifier / inorganic nano powder extruded by a screw extruder, and drying to obtain a hydrophobic sealing film material;
[0071] 4) The hydrophobic sealing film material was placed in a film casting machine, the casting extrusion temperature was set to 220° C., and a film sample with a thickness of 0.1 mm was extruded. The test results of the film sample are shown in Table 1.
[0072] Comparative Example 1
[0073] 100 parts by mass of polyethylene resin (melt flow rate at 210°C: 4 g / 10 min, elongation at break: 250%, brand: LD160AS, origin: Beijing Yanshan Petrochemical Co., Ltd., Sinopec Group) was weighed and placed in a film casting machine. The casting extrusion temperature was set to 220°C and extruded into a film sample with a thickness of 0.1 mm. The test results of the film sample are shown in Table 1.
[0074] Comparative Example 2
[0075] The test results of the commercially available Parafilm sealing film (brand number: PM996, origin: Bemis Inc., USA) are shown in Table 1.
[0076] Performance Testing
[0077] The testing process and method of the film samples prepared in the above embodiments and comparative examples are as follows:
[0078] For the test of pure water contact angle of film samples: the test is carried out according to GB / T 30447-2013 "Nanofilm Contact Angle Measurement Method". At room temperature, the test sample is placed horizontally under the objective lens of the contact angle meter, and the contact angle of the blend system to pure water is tested with ultrapure water.
[0079] For the test of the mechanical properties of the film samples: the test is carried out in accordance with GBT1040-2006 "Determination of tensile properties of plastics". The tensile rate is 50mm / min and the test temperature is 23-25℃.
[0080] For the test of the windability of the film sample: cut a film sample with a length of 100mm, a width of 10mm, and a thickness of 0.03mm, and fold it repeatedly along the long side to form a strip with a length of 100mm and a width of 2.5mm. After one end of the strip intersects with the rest of the strip to form a ring, the head of the strip passes through the ring and is gradually tightened to form a knot, and then the knot is tightened to form a single knot for the test of the windability of the film sample; after the two ends of the strip are crossed and wound, they are wound again above the cross, and finally the two ends of the strip are held and gradually tightened to form a flat knot for the test of the windability of the film sample. After the test sample is placed naturally at room temperature for 7 days, observe whether the knot slips.
[0081] For the test of film sample wrapping and laminating durability: refer to GB / T 4851-1998 "Test method for adhesion of pressure-sensitive adhesive tapes" for testing. Cut the film sample to be tested into a sample with a width × length of 10mm × 150mm, slightly stretch it and wrap it around a glass test tube with a diameter of 2cm. After leaving it naturally at room temperature for 7 days, observe whether the end of the wrapped film sample is lifted, whether the film sample has stress relaxation, slippage, etc.
[0082] Table 1 Test results of film samples
[0083]
[0084]
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hydrophobic sealing film material, characterized in that: The method is prepared by melt blending raw materials, which include, by weight: The polyethylene resin and the polyisobutylene resin in the hydrophobic sealing film material are a dual-continuous phase structure in terms of microscopic thermodynamic phase structure, and the solid paraffin is dispersed in the resin continuous phase structure in an island-like structure.
2. The hydrophobic sealing membrane material according to claim 1, characterized in that: The polyethylene resin is a low-density polyethylene resin; the melt flow rate of the polyethylene resin at 210° C. is 4 to 20 g / 10 min; and the elongation at break of the polyethylene resin is not less than 200%.
3. The hydrophobic sealing membrane material according to claim 1, characterized in that: The number average molecular weight of the polyisobutylene resin is 400-5000.
4. The hydrophobic sealing membrane material according to claim 1, characterized in that: The melting point of the solid paraffin is 50-70°C.
5. The hydrophobic sealing membrane material according to claim 1, characterized in that: The compatibilizer is at least one of SIS petroleum resin, EPDM rubber, EPDM rubber, polyolefin elastomer, styrene-butadiene block copolymer and hydrogenated styrene-butadiene block copolymer.
6. The hydrophobic sealing membrane material according to claim 1, characterized in that: The nano-opening modifier is at least one of nano-silicon dioxide, nano-montmorillonite, nano-wollastonite, nano-titanium dioxide, nano-zinc oxide and nano-calcium carbonate; the particle size of the nano-opening modifier is 400-1000 meshes.
7. The hydrophobic sealing membrane material according to claim 1, characterized in that: The micro-crosslinking modifier is at least one of dibenzoyl peroxide, dicumyl peroxide and azobisisobutyronitrile.
8. The hydrophobic sealing membrane material according to claim 1, characterized in that: The hydrophobic modifier is at least one of a fatty acid compound, a silane compound and a thiol compound.
9. A method for preparing a hydrophobic sealing membrane material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Polyethylene resin, polyisobutylene resin, solid paraffin, a compatibilizer, a nano-opening modifier, a micro-crosslinking modifier and a hydrophobic modifier are melt-blended to obtain a hydrophobic sealing film material.
10. A hydrophobic sealing film, characterized in that: The material of the hydrophobic sealing membrane is the hydrophobic sealing membrane material according to any one of claims 1 to 8.